The 1954 Geneva agreement on vietnam and the 1973 paris agreement: diplomacy and the triumph of the vietnamese revolution - Asselin, Pieere (VNU Journal of Science: Social Sciences and Humanities; Vol 22 No 5E, 2006)
Abstract